Relationship Between Waiting Time for Compounded and Non-Compounded Prescriptions and Patient Satisfaction in an Outpatient Pharmacy - Ocayana, Baiq Tia; Tusshaleha, Lelie Amalia; Bayani, Faizul (THRIVE Health Science Journal, 2026)
Efficient pharmaceutical services are essential in hospitals to ensure patient satisfaction and improve healthcare outcomes. Prescription waiting time, both compounded and non-compounded, is a critical indicator of pharmacy service quality. This study aimed to analyze the relationship between prescription waiting times and patient satisfaction at the outpatient pharmacy of RSUD Awet Muda Narmada. Using a correlational analytic design with a cross-sectional approach, 100 patients were selected through accidental sampling. Data were collected via questionnaires and direct time measurements, then analyzed with Chi-Square tests. Results revealed that 80% of respondents were very satisfied with services received, and 95% experienced acceptable waiting times. The average waiting time was 41.7 minutes for compounded prescriptions and 12.3 minutes for non-compounded prescriptions. Statistical analysis showed a significant relationship (p=0.000) between waiting time and patient satisfaction. These findings suggest that efficient waiting time management significantly influences satisfaction levels. Therefore, optimizing pharmacy workflow, increasing human resources, and adopting technology-based systems may further enhance service quality and patient experiences.